Questioning the History of the Bildungsroman with Pierre Bourdieu (KULT_online, 2017)
The edited volume Der Bildungsroman im literarischen Feld sketches an alternative history of the ‘Bildungsroman’ genre through a careful observation of reception and secondary literature. By applying Pierre Bourdieu´s field theory, the book depicts the German literary world as a literary field where the authors as social agents are fighting over positions. It traces the development of the German Bildungsroman from its beginning until today, asking how it happens that some novels are considered central in the genres canon, while others with exactly the same textual features are not. This innovative approach proves to be convincing and develops a theoretical framework that seems promising for dealing with future questions about the development and differentiation of literary genres.